Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/jcm11154460
|View full text |Cite
|
Sign up to set email alerts
|

Is Evar Feasible in Challenging Aortic Neck Anatomies? A Technical Review and Ethical Discussion

Abstract: Background: Endovascular aneurysm repair (EVAR) has become an accepted alternative to open repair (OR) for the treatment of abdominal aortic aneurysm (AAA) despite “hostile” anatomies that may reduce its effectiveness. Guidelines suggest refraining from EVAR in such circumstances, but in clinical practice, up to 44% of EVAR procedures are performed using stent grafts outside their instruction for use (IFU), with acceptable outcomes. Starting from this “inconsistency” between clinical practice and guidelines, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Numerous studies have demonstrated that standard EVAR for AAA patients with an HNA can nevertheless achieve satisfactory long-term outcomes, confirming the efficiency of EVAR in cases of unfavourable morphologies [ 15 , 16 ]. However, the increased incidence of ELIa has been linked to a hostile neck anatomy due to an insufficient seal between the aortic wall and the endograft attachment sites [ 8 , 17 ].…”
Section: Discussionmentioning
confidence: 92%
“…Numerous studies have demonstrated that standard EVAR for AAA patients with an HNA can nevertheless achieve satisfactory long-term outcomes, confirming the efficiency of EVAR in cases of unfavourable morphologies [ 15 , 16 ]. However, the increased incidence of ELIa has been linked to a hostile neck anatomy due to an insufficient seal between the aortic wall and the endograft attachment sites [ 8 , 17 ].…”
Section: Discussionmentioning
confidence: 92%
“…Numerous studies have demonstrated that standard EVAR for AAA patients with a hostile neck anatomy can nevertheless achieve satisfactory long-term outcomes, con rming the e ciency of EVAR in unfavorable morphologies. 14,15 However, the increased incidence of type Ia endoleak was linked to a hostile neck anatomy, which resulted from an insu cient seal between the aortic wall and the endograft attachment sites. 8,16 This retrospective study assessed the short-term e cacy and safety of intraprocedural selective coil embolization of the aneurysmal sac neck to eliminate persistent type Ia endoleak in endovascular repair of AAA with hostile neck morphology.…”
Section: Discussionmentioning
confidence: 99%
“…However, as for standard EVAR in challenging anatomies [3], the main disquietude regarding complex endovascular aortic repair procedures should be represented by the mid‐ and long‐term follow‐up.…”
mentioning
confidence: 99%